Organisational Dimensions in Cross Sector Partnerships - Harding, R. C (2010)
Cross sector partnerships (CSPs) are becoming an increasingly prominent and distinct aspect of corporate social responsibility (CSR) strategies. However, despite their importance, the majority of these collaborations are short lived and deteriorate before their expected potential can be reached. An extant and burgeoning literature surrounding CSPs has developed to address this hurdle. A critical review of this partnership literature demonstrates the organisational dimension, organisational culture, is frequently cited as a principle barrier to CSP success. However as will be revealed, analyses upon which this opinion is based make no detailed attempt to examine organisational culture which has resulted in a failure to recognise the significance of organisational identity. This investigation will argue that organisational culture cannot be considered in isolation from organisational identity which if overlooked results in the former being incorrectly conceived as an isolated, static and dormant entity. It is this unitary culture assumption that has come to dominant the partnership literature and for these reasons it is believed that the partnership literature is limited in its understanding of CSPs. Instead, a socially constructed viewpoint of organisational culture is adopted, one which recognises the prominent role that organisational identity plays throughout the CSP process. To demonstrate the significance of organisational identity, discursive and behavioural identity processes are observed through the wider setting of an action research project between Paul Smith Limited and The Meadows Partnership Trust. Three dominant identity narratives were discovered to have a prevailing influence upon the direction and development of the CSP, namely ‘Family and Altruism’, ‘Classic with a Twist’ and ‘Protective and Pride’. Through analysing these identity narratives, it is apparent that they are grounded in and guided by organisational culture yet by being the creation of organisational identity are fluid, temporal constructs which adapt and modify in accordance to the new organisational situation of a CSP. A realisation of the significance of organisational identity throughout CSPs offers a more authentic portrayal of CSPs which if applied could aid in the implementation of future CSPs.